An Environmental-Economic Assessment of Genetic Modification of Agricultural Crops - Jeroen C.J.M. van den Bergh; Justin M. Holley (Tinbergen Institute, 2001)
The advantages and disadvantages of genetic modification of organisms in agriculture are reviewed. These relate to the environment, human health, socio-economic effects, population growth, and differential consequences for developed and developing countries. An overall evaluation requires that attention is given to the perception and endogeneity of uncertainty, irreversibility, the availability of alternatives, and a comparison with other complex issues. Some implications for an effective public strategy are outlined.
Keywords: 330; Biotechnology; Cost-benefit analysis; Ecology; Evolution; Genetic engineering; Health; Irreversibility; Transgenic plants; Uncertainty; Landwirtschaft; Gentechnik; Umweltökonomik; Kosten-Nutzen-Analyse; Theorie